STUDY OF THE INTENSITY OF THE LIGHT FLOW OF DENTAL PHOTOPOLYMERIZERS - O.A. Udod; H.M. Alihadzhyieva; V.M. Talanov (Український стоматологічний альманах, 2024)
Relevance. During the direct restoration of teeth with light-curing composites, it is important to irradiate them from the minimum distance to ensure a sufficient amount of light energy for curing, but this is not always achievable.